Authority or authoritarian? Reflections from the regency stage in History in Elementary School II (Research, Society and Development, 2020)
The present article is based on the experience achieved in the stage of regency in Elementary School II, in the subject of History. By means of time and space cutoff in the set of situations experienced in the stage restrict a case of a subject like a source of reflective stimulation. Therefore, was established the problematic: if the case evidence before questions to besides subject. Then, we aimed to describe and reflect on the situation; realize the dialog classic between theory and practice to seek possible lines of comprehension of the situation. The method explanatory case study was used, the hermeneutic debate inside the historiography area, and the self-assessment about our in a posture of regency. Concomitantly, we used the bibliographic revision assumptions and annotations of citations. We develop on three lines of results: indiscipline, the challenge of authority, and the exercise of authoritarian authority. In the end, we toke indications and contributions to avoid the practice of authoritarian authority and subject in class.